Management of Lobular Neoplasia Diagnosed by Core Biopsy. (18th April 2023) - Jani, Chinmay; Lotz, Margaret; Keates, Sarah; Gupta, Yasha; Walker, Alexander; Al Omari, Omar; Parvez, Arshi; Patel, Dipesh; Gnata, Maria; Perry, John; Khorashadi, Leila; Weissmann, Lisa; et al.
Abstract : Lobular neoplasia (LN) involves proliferative changes within the breast lobules. LN is divided into lobular carcinoma in situ (LCIS) and atypical lobular hyperplasia (ALH). LCIS can be further subdivided into three subtypes: classic LCIS, pleomorphic LCIS, and LCIS with necrosis (florid type). Because classic LCIS is now considered as a benign etiology, current guidelines recommend close follow-up with imaging versus surgical excision. The goal of our study was to determine if the diagnosis of classic LN on core needle biopsy (CNB) merits surgical excision. This is a retrospective, observational study conducted at Mount Auburn Hospital, Cambridge, MA, from May 17, 2017, through June 30, 2020. We reviewed the data of breast biopsies conducted at our hospital over this period and included patients who were diagnosed with classic LN (LCIS and/or ALH) and excluded patients having any other atypical lesions on CNB. All known cancer patients were excluded. Of the 2707 CNBs performed during the study period, we identified 68 women who were diagnosed with ALH or LCIS on CNB. CNB was performed for an abnormal mammogram in the majority of patients (60; 88%) while 7(10.3%) had an abnormal breast magnetic resonance imaging study (MRI), and 1 had an abnormal ultrasound (US). A total of 58 patients (85%) underwent excisional biopsy, of which 3 (5.2%) showed malignancy, including 2 cases of DCIS and 1 invasive carcinoma. In addition, there was 1 case (1.7%) with pleomorphic LCIS and 11 cases with ADH (15.5%). The management of LN found on core biopsy is evolving, with some advocating surgical excision and others recommending observation. Our data show a change in diagnosis with excisional biopsy in 13 (22.4%) of patients with 2 cases of DCIS, 1 invasive carcinoma, 1 pleomorphic LCIS, and 9 cases of ADH, diagnosed on excisional biopsy. While ALH and classic LCIS are considered benign, the choice of ongoing surveillance versus excisional biopsy should be made with shared decision making with the patient, with consideration of personal and family history, as well as patient preferences.